2018
DOI: 10.24891/fa.11.3.313
|View full text |Cite
|
Sign up to set email alerts
|

Some issues of the methodology for assessing budget risks

Abstract: Ключевые слова: бюджетный риск, идентификация, нормативное-правовое регулирование, оценка Аннотация Тема. Предметом исследования выступают бюджетные риски, унифицированная методика оценки и идентификация которых является необходимым условием совершенствования управления общественными финансами. Рассмотрены подходы к оценке бюджетных рисков, учитываемые в российском правовом поле. Основное внимание уделяется несовершенству государственной регламентации идентификации и оценки бюджетных рисков. Отдельные разделы … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The topic of budget risks has received wide coverage in the works of domestic and foreign scientists. Some studies have been devoted to the theory of budget risks and their assessment (Gamukin [2]; Solomkoi I., Solomko M. [3]; Omelyohina [4]; Frumina [5]; Kot, Zyryanova, Terekhova [6]; Khanina [7]; Yanov [8]). Other studies have revealed the specificity of budget risks at the territorial level and ways to minimize them (Lebedeva [9]; Korobko [10]; Chernyakova [11]; Gorokhova [12]; Stepanova [13]; Ok, Moo-Seok [14]).…”
Section: Introductionmentioning
confidence: 99%
“…The topic of budget risks has received wide coverage in the works of domestic and foreign scientists. Some studies have been devoted to the theory of budget risks and their assessment (Gamukin [2]; Solomkoi I., Solomko M. [3]; Omelyohina [4]; Frumina [5]; Kot, Zyryanova, Terekhova [6]; Khanina [7]; Yanov [8]). Other studies have revealed the specificity of budget risks at the territorial level and ways to minimize them (Lebedeva [9]; Korobko [10]; Chernyakova [11]; Gorokhova [12]; Stepanova [13]; Ok, Moo-Seok [14]).…”
Section: Introductionmentioning
confidence: 99%